Analysis of Network Threats that Effect the Bandwidth Utilization in UniMAP Student Campus - Mohammad Taufik, Saidina Omar (2010)
Threats can happen everywhere. Same goes to the IT environment where the networking part is the most critical. It is because; network threats like viruses, spywares and forbidden application are using the network to launch the attack silently. A study has been done in Universiti Malaysia Perlis (UniMAP) where one of the student hostels is identified for the place to do the network analysis. The hostel name is Kolej Kediaman Tan Sri Aishah Ghani (KKG) located in Wang Ulu, Perlis. The students have been complaining that the network quality is going very slow and they cannot access to the internet and the internal application like UniMAP Portal, UniMAP website and email smoothly. To overcome this, a network security appliance is obtained to perform the network traffic analysis in order to identify the type of network activity that has congested the KKG network system. A network policy has been applied to deny any unwanted threats, forbidden application usage and access to the bad host.